An Interview with Miriam Schcolnik: Reading, E-Reading and Writing and Their Assessment - Shaughnessy, Michael F. Shaughnessy (European Scientific Journal, ESJ, 2020)
Dr. Miriam Schcolnik (emerita) is the former Director of the Language Learning Center of the Division of Foreign Languages at Tel Aviv University. For three decades she coordinated and taught EAP (English for Academic Purposes) courses as well as a course in Technology in Language Teaching. She has developed many online learning environments, multimedia courseware packages, EFL textbooks, and teachers’ resource books. Her research interests are e-reading and writing, and the use of digital tools to facilitate language learning and communication.